Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/biom12101453
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Neuroinflammation in Osteoarthritis with Intra-Articular Adelmidrol

Abstract: Neuroinflammation is an emerging therapeutic target in chronic degenerative and autoimmune diseases, such as osteoarthritis (OA) and rheumatoid arthritis. Mast cells (MCs) play a key role in the homeostasis of joints and the activation of MCs induces the release of a huge number of mediators, which fuel the fire of neuroinflammation. Particularly, synovial MCs release substances which accelerate the degradation of the extra-cellular matrix causing morphological joint changes and cartilage damage and inducing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Neuroinflammation is mediated by the release of pro-inflammatory cytokines by non-neuronal cells, such as astrocytes and microglia, which represents the innate immune system of the central nervous system. Neuroinflammation may also involve peripheral immune cells, like mast cells, which, when hyper-activated, may release many pro-inflammatory cytokines and immunomodulators, such as TNF-alpha, IL-6, IL-8, VEGF, histamine, heparin, and tryptase, which play a determinant role in the progression of osteoarthritis (OA) by promoting subcondral erosions, synoviocyte proliferation, angiogenesis, and pain sensitization [289]. Age and frailty are risk factors for the development of OA, which is a leading cause of chronic pain in the elderly [290].…”
Section: Frailty and Chronic Painmentioning
confidence: 99%
“…Neuroinflammation is mediated by the release of pro-inflammatory cytokines by non-neuronal cells, such as astrocytes and microglia, which represents the innate immune system of the central nervous system. Neuroinflammation may also involve peripheral immune cells, like mast cells, which, when hyper-activated, may release many pro-inflammatory cytokines and immunomodulators, such as TNF-alpha, IL-6, IL-8, VEGF, histamine, heparin, and tryptase, which play a determinant role in the progression of osteoarthritis (OA) by promoting subcondral erosions, synoviocyte proliferation, angiogenesis, and pain sensitization [289]. Age and frailty are risk factors for the development of OA, which is a leading cause of chronic pain in the elderly [290].…”
Section: Frailty and Chronic Painmentioning
confidence: 99%
“…Recent evidence supports the in vivo antioxidant activity of ADM in animal models of colitis [30], ischemia/reperfusion injury [31] and pulmonary fibrosis [32], but the antioxidant protective effect has not yet been investigated at the molecular and cellular level. Recent preclinical and clinical studies have shed some light on the benefit of a new intra-articular formulation based on high molecular weight HA (1%) and ADM (2%) in osteoarthritis [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the cartilage is not innervated, OA pain is probably due to changes in the underlying bone and synovial inflammation [ 2 ]. Recent research revealed the crucial role of synovial inflammation in both OA incidence and progression and also in the genesis of pain [ 4 , 5 , 6 ]. Joint cells, such as synoviocytes, inflammatory cells (mast cells and macrophages), and chondrocytes, as well as infrapatellar fat pads that produce chemokines, cytokines, and proteases, which can initiate and maintain synovial inflammation, contribute to cartilage damage and sensitize primary afferent fiber terminals in adjacent tissues [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%